PESAN DAKWAH SUNAN KALIJAGA: Analisis Konten Buku Mistik dan Makrifat karya Achmad Chodjim - Malik, Muhamat Abdul; Warsah, Idi; Kamil, Pajrun (BINA' AL-UMMAH, 2020)
The aim of this study was to analyze the contents of a book by Achmad Cholidjim concerning Sunan Kaligaja’s mystical and makrifat teachings so that da’wah-related messages could be found either explicitly or implicitly as presented in the book. This study used a non-interactive qualitative approach because it only examined the contents of the book. The main source of data in this study was a book by Achmad Chodjin entitled “Sunan Kalijaga: Mystical and Makrifat”. This study concluded that the contents of Sunan Kalijaga’s da’wah messages contained in Achmad Chodjim's book titled “Sunan Kalijaga: Mystical and Makrifat” contained syari’at, tarekat, and hakekat combined together. Sunan Kalijaga used his own method to spread Islam especially in Java. He used Javanese language and culture in da'wah. Thus, Javanese people would more easily understand his teachings, and they were not away from the sunnah of Allah and His prophets. Sunan Kalijaga also advised that every Muslim practice and apply the Islamic teachings as explained in the Qur'an and Hadith.